Culturally Responsive Teaching: Connecting Mathematics to Art (pp. 7–17) - Wachira, Patrick W (Ohio Journal of School Mathematics, 2020)
The author presents an activity designed to help preservice mathematics teachers begin to understand how they can make their lessons more culturally responsive by connecting content to everyday contexts while incorporating students’ interests and culture in their teaching.